Who is this who is coming? From neurosis to neurodegeneration in television adaptations of M. R. James's 'Oh, Whistle and I'll Come to You, My Lad'. Issue 3 (1st October 2021) - Ray, Nicholas
This article discusses two BBC television adaptations of M. R. James's classic ghost story 'Oh, Whistle and I'll Come to You, My Lad' (1904), the first directed by Jonathan Miller (1968) and the second by Andy de Emmony (2010). Arguing that de Emmony's film takes Miller's as a point of departure, it attempts to track the progressive 'psychologization' of James's tale, a development that it explores with reference to Sarah Cardwell's notion of 'meta-textual' lineage. The article outlines how Miller knowingly reimagines James's story as a Freudian parable by drawing on the resources of classical psychoanalysis and its understanding of neurosis as the expression of a dynamic interior conflict, one in which something repressed menacingly returns. It goes on to read de Emmony's film, which reorganizes the story around a case of dementia, as an effort to extend the tale into the psychic terrain of the 'new wounded', a term coined by philosopher Catherine Malabou to describe emergent psychopathologies unique to neurological injury or degeneration. Taking conceptual support from Malabou, the article demonstrates both the self-consciousness with which the later adaptation builds from its antecedent and its reinscription of the story within a frame of reference that specifically exceeds the psychoanalytic ontology presupposed by Miller. The films reimagine and contemporize the Jamesian haunting ‐ with its climactic coming of a mysterious other ‐ in ways that are utterly distinct but also cumulatively psychological. Looked at in apposition, the article suggests, they exemplify adaptation not simply as a revival or reconstitution of a past text but as an ongoing, intertextual and incremental labour of reinvention.